Set for life : financial peace for people over 50 - Holzer, Bambi (John Wiley & sons New YorkUS, 2000)
Provides the age 50+ American population with guidelines for building and preserving their wealth. Addresses various finance matters including: planning; self-assessment; understanding and managing investments; additional sources of income during retirement; taxes and insurance; health care and daily living; and, distribution of assets.